(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Tooth-wear signatures obtained from maxillary carnassial fourth premolar teeth of raccoons in three ecologic regions in Nigeria testified to segregations in diet of the species with more abrasive diet in specimens from coastal south-western areas compared to more vegetal diet content of those from middle belt and northern areas. Endoloph assessments showed sexually dimorphic mesowear signals between and within locations suggestive that males are more exposed to dental wears compared to females; Male and female specimens from rainforest zone had 40.2% and 34.2% respectively, Sudan Savanna zone had 46.8% and 40.6% for females and males while 67.6% and 44.3% for Sahel zone specimens in similar order. We investigated dietary resource use for sustained survivability within limits of interspecific spatial overlaps using seasonal rainfall indices between two years. There was 86% per high dental occlusal surface relief in the specimens from the savannas while 32% per low relief was observed in South-Western badgers teeth samples. This study observed a change in habitat use as a predisposing factor to sub-regional dental wear differences among age groups as well as sexes of species from three geographic climatic areas. The richness of the eco-habitat/life expectancy found in the rain forest can be ascribed to diet availability which is reduced in the savanna areas. The study suggests minimal change in habitat use as a predisposing factor in sub-regional species dental relief differences observed among age groups and sexes of the species from three geographic climatic areas and also represents quality of the eco-habitats.